PENGARUH KARAKTERISTIK AUDIT EKSTERNAL PADA PRICE TO EARNINGS RATIO PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hartawan, Nyoman Yudhi; Yadnyana, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.01.TAHUN 2015, 2015)
ABSTRACT   Market tends to respond positively to higher audit quality. Higher audit quality is expected to be achieved if audit tenure is relatively short, audit is conducted by large audit firms, and auditor provides unqualified audit opinion. This study aims to examine the effect of external audit characteristics (audit tenure, public accounting firms size, and audit opinion) on price to earnings ratio of companies listed on the Indonesian Stock Exchange from 2008 to 2012 with two controlling variables (company or client size and age). The population in this study is companies that have been listed on the Indonesian Stock Exchange from 2008 to 2012 wehereas sample is selected by purposive sampling method under two underlying criteria: the companies have been consistently listed on the Indonesian Stock Exchange between 2008 and 2012 and companies provide all required data for this study purpose. The hypotheses are tested by multiple linear regression technique to test the model before and after including controlling variables. The test shows that audit tenure has no affects price to earnings ratio, public accountng firms size positively affects price to earnings ratio, and audit opinion has no affects price to earnings ratio.   Keywords :   audit tenure, public accounting firms size, audit opinion, company or client size, company or client age, price to earnings ratio
Keywords: audit tenure, public accounting firms size, audit opinion, company or client size, company or client age, price to earnings ratio